2001
DOI: 10.1007/s004250000455
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-membrane H + -ATPases are expressed in pitchers of the carnivorous plant Nepenthes alata Blanco

Abstract: Nepenthes is a unique genus of carnivorous plants that can capture insects in trapping organs called pitchers and digest them in pitcher fluid. The pitcher fluid includes digestive enzymes and is strongly acidic. We found that the fluid pH decreased when prey accumulates in the pitcher fluid of Nepenthes alata. The pH decrease may be important for prey digestion and the absorption of prey-derived nutrients. To identify the proton pump involved in the acidification of pitcher fluid, plant proton-pump homologs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…For the fluid samples of NAM, the acidic fluids consistently found in this work were similar to those found in a previous study [8]. It has been reported that the pH fluctuations of the pitcher fluids may be induced by prey captured, e.g., from pH 5.5 to 3.0 in Nepenthes [35] and also may be caused by H + secretion from living epidermis cells [36,37]. Moreover, ants which were found as a major prey may be of importance, as a constant import source of formic acid which lowers the pH of the pitcher fluid and possibly raises the redox potential [38].…”
Section: Discussionsupporting
confidence: 86%
“…For the fluid samples of NAM, the acidic fluids consistently found in this work were similar to those found in a previous study [8]. It has been reported that the pH fluctuations of the pitcher fluids may be induced by prey captured, e.g., from pH 5.5 to 3.0 in Nepenthes [35] and also may be caused by H + secretion from living epidermis cells [36,37]. Moreover, ants which were found as a major prey may be of importance, as a constant import source of formic acid which lowers the pH of the pitcher fluid and possibly raises the redox potential [38].…”
Section: Discussionsupporting
confidence: 86%
“…The food webs of pitchers from these different families on different continents are more like each other than they are like the food webs of other aquatic microcosms, even if the microcosms are in the same habitat as the pitchers [50]. Convergence might be influenced by the plants' internal chemistry, which is similar among all pitcher plant lineages and is controlled to some extent by the plant [51][52][53].…”
Section: Examples Of Convergent Interactionsmentioning
confidence: 99%
“…0.1 mm in diameter, and are densely localized on the inner surface of the lower part of the pitcher . Recently, the plasma membrane H + -ATPase (An et al 2001) and ammonium transporter (Schulze et al 1999) were found to be expressed in the glands, further suggesting that the glands are indeed important for acid secretion and nutrient absorption.…”
Section: Introductionmentioning
confidence: 98%